Holistic approach in Integrated Landscape Design. - Case Study for Montalvão Urban Park at Castelo Branco – Portugal - Matos, Rute (2017)
This paper is the result of a theoretical research on the concept of landscape from a more comprehensive and general view, as an introduction to Mediterranean landscape, and more specifically, Portuguese landscape, which is included in the former. Some concepts are addressed by several national and international authors in order to get to the concept of landscape that we defend – holistic and multi-functional –, within which Mediterranean landscape, and within which Portuguese landscape is a paradigm. Since landscape is identity, the development of a nation, and a reflex of their culture, we deem it fundamental for landscape to continue being an identity and sustainable in spite of the general globalisation which we are witnessing, and to continue reflecting the will of the people. Hence, on this assumption, as well as bibliographic research, we have used the Portuguese common landscape as a concept for the construction of a space with contemporary landscape – Parque Urbano de Montalvão, in Castelo Branco –, which is the object of a tender. We hereby consider that the submitted bid recognises the value, character, and essence of this place, hence contributing with all that is necessary to safeguard the region’s identity.